Penile Reconstruction: Evaluation of the Most Accepted Techniques - Babaei, Ali Reza; Safarinejad, Mohammad Reza; Farrokhi, Farhat; Iran-Pour, Elham (Urology Journal, 2010)
Purpose: Loss of the penis can have a devastating effect on the lives of sufferers with significant psychogenic implications. Penile reconstruction or phallus construction poses a difficult challenge and a demanding problem to the urologists and plastic surgeons. Different techniques have been used for construction of a total penis and reconstruction of severely injured penis. The objective of this review was to determine the efficacy, advantages and disadvantages of the most popular penile reconstruction (PR) and phallus construction techniques. Materials and Methods: We searched without language restriction MEDLINE, Pre-MEDLINE EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) from January 1960 to January 2009. In addition, we searched the citation lists of relevant articles and book chapters. Studies evaluating the functional and cosmetic results of different techniques of total phallus construction (TPC) and penile reconstruction (PR) were identified. Two authors independently evaluated studies for selection, study quality, and extracted data. The primary outcome was creation of a sensate and cosmetically acceptable phallus. The secondary outcomes were competent neourethra that allows voiding in comfortable position, sexual intercourse, and the rate of complications. Results: One hundred and forty-six studies with a total of 1622 patients were included in this review. Conclusion: Data from the available studies are insufficient to recommendany technique for TPC or PR. In the absence of evidence to support any method, the review authors recommend the one-stage TPC or PR. Further studies are warranted, preferably multi-centered studies.